Staphylococcus aureus - Na'was, Tarek (2015)
Staphylococcus aureus isa gram positive coccus thathas long been associated with many serious infections amongst which foodborne illnesses are common. The enteric pathogenicity of this bacterium is mediated mainly by its production of various enterotoxins. The role of S.aureus in causing numeroustypes of infections and its ability to rapidly become resistant to antibacterial agents have shadowed its association with food poisoning. This study, which aimed at detecting the prevalence of S.aureusin coleslaw, a salad commonly served in the restaurants in the Ras-Beirut area, revealed alarming results. Of the 37 samples tested, 32 (86.5%) were positive for the presence of S.aureus. Although the isolated strains were not tested for enterotoxin production, yet such a high prevalence is a clear indicator of the lack of application of proper sanitary protocols in the tested food outlets.